2012
DOI: 10.2466/06.15.pms.115.5.661-675
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Perceptions of Neighborhood Walkability among Turkish Women in Low and High Socio-Economic Environments: An Exploratory Study

Abstract: The purpose of this study was to compare the levels of physical activity, exercise stages of change, and perceptions of neighborhood walkability among Turkish women who were living in low and high socio-economic (SES) environments. The participants included 188 women in low SES and 206 in high SES environments, between the ages of 18 and 65 years. The Low SES group had a higher rate of inactivity, and relative to the High SES group, was less likely to rate the neighborhood environment as promoting and supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Few studies have examined factors associated with physical activity among Turkish adults. In one study, Yildirim, Ince, and Muftuler () reported that moderate and total physical activity levels were higher among women from high socioeconomic status (SES) neighborhoods ( p = .01). Women living in high SES neighborhoods had higher environmental scores for characteristics such as aesthetics, infrastructure for safety and walking, and street connectivity, whereas those from low SES areas had higher scores for traffic hazards and crime perception (Yildirim et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined factors associated with physical activity among Turkish adults. In one study, Yildirim, Ince, and Muftuler () reported that moderate and total physical activity levels were higher among women from high socioeconomic status (SES) neighborhoods ( p = .01). Women living in high SES neighborhoods had higher environmental scores for characteristics such as aesthetics, infrastructure for safety and walking, and street connectivity, whereas those from low SES areas had higher scores for traffic hazards and crime perception (Yildirim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Yildirim, Ince, and Muftuler () reported that moderate and total physical activity levels were higher among women from high socioeconomic status (SES) neighborhoods ( p = .01). Women living in high SES neighborhoods had higher environmental scores for characteristics such as aesthetics, infrastructure for safety and walking, and street connectivity, whereas those from low SES areas had higher scores for traffic hazards and crime perception (Yildirim et al, ). In another study of nurses in Turkey, intrapersonal factors of BMI, number of cigarettes smoked after starting work, alcohol consumption, and fast‐food consumption, as well as the interpersonal factor of presence of cancer in the family were associated with physical activity habits (Yilmaz, Kumsar, Sen, Karakaplan, & Leymun, ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of adherence is definitely influenced by logistic difficulties, namely the state and presence of public transport and how it can be challenging to utilize public transportation on a regular basis for a patient with cardiovascular problems. Moreover, it must also be kept in mind that patients in Turkey are not as active as they should be, with exercise habits differing significantly from patients in elsewhere in the world, and the level of activity is heavily influenced by socioeconomic factors (15,16). It has been shown that in the results of the Danish registry, patients older than 70 years, retired, low educated and with a lower annual income are less willing to participate in CR programs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have demonstrated a facilitative effect of the street environment on the physical activity of older adults in areas with high SES (70,71). Neighborhoods with low SES lack relevant infrastructure due to pollution, which results in a negative association between the built environment and physical activity in older adults (35).…”
Section: Literature Review 21 Research Related To the Impact Of The B...mentioning
confidence: 99%